Socioeconomic factors as predictors of creative thinking in teenagers: a study in the Kazakh context - Kuspanova, Aikun; Abdimanapov, Bakhadurkhan; Kaimuldinova, Kulyash; Atasoy, Emin; Savanchiyeva, Armanay (Institute of Advanced Engineering and Science, 2025)
This study investigates the influence of socioeconomic factors on the creative thinking of teenagers in Kazakhstan, as perceived by parents and teachers. Creative thinking is recognized as a vital skill in modern education, yet its relationship with socioeconomic factors remains underexplored in the Kazakh context. This research addresses this gap by examining how school and family environments, shaped by socioeconomic status (SES), impact teenagers' creative abilities. Using a combination of open and closed-ended questionnaires, data were collected from 121 parents and 922 teachers across Kazakhstan. Spearman correlation analysis revealed a significant relationship between SES and creative thinking, with higher socioeconomic conditions correlating with greater creativity. These findings suggest that enhancing socioeconomic conditions in educational and family settings can foster creative thinking in teenagers. The study concludes by emphasizing the need for targeted educational policies that address socioeconomic disparities to support creative development in students.